2012
DOI: 10.1063/1.4724213
|View full text |Cite
|
Sign up to set email alerts
|

Graphene folds by femtosecond laser ablation

Abstract: We report the production of graphene folds induced by femtosecond laser ablation. A single laser pulse irradiation on graphene produced an ablated spot featuring in its proximity circumferentially periodic graphene folds. The graphene fold structure was constructed through folding of a single layer graphene segment. We investigated the laser fluence effect on the graphene fold structure. We also performed ablation on suspended graphene and verified that interaction with the underlying substrate is required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
53
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 18 publications
3
53
0
3
Order By: Relevance
“…The slightly elevated increase of the defect D-band in (B) and (C) (and the broader G-band in (C)) indicates higher disorder in the lattice structure that originates both from edge effects 19,21 and folding in accordance with observations by other groups. 13,15 In Fig. 2(e), we plot the Raman spectra peak intensities [19][20][21] (respectively, D, G, and 2D-bands as highlighted in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The slightly elevated increase of the defect D-band in (B) and (C) (and the broader G-band in (C)) indicates higher disorder in the lattice structure that originates both from edge effects 19,21 and folding in accordance with observations by other groups. 13,15 In Fig. 2(e), we plot the Raman spectra peak intensities [19][20][21] (respectively, D, G, and 2D-bands as highlighted in Fig.…”
mentioning
confidence: 99%
“…11,12 Previous studies of ultrafast laser ablation of graphene have shown that pristine and chemical vapor deposition (CVD) graphene have well defined ablation thresholds over which clean ablation is performed with no residues whereas, below this threshold, defects are formed and serve as initiating centers for ablation by consecutive pulses. [13][14][15] Using this cumulative effect, a range of structures including micro-and nano-ribbons and nanodots have been processed in graphene using femtosecond lasers in the kHz and MHz regimes. 12,16 Although the threshold effect in the single shot regime can be used to generate nanostructures of dimension well below the laser wavelength, the precise positioning of the sample with respect to the laser beam waist is an extremely severe constraint.…”
mentioning
confidence: 99%
“…Micron-scale holes are observed, with the boundary showing curled/folded edges as reported previously. 25 Also shown are the electron diffraction patterns used to determine the crystallographic orientation of the graphene. We label zigzag edges with orange lines and armchair edges with magenta lines.…”
mentioning
confidence: 99%
“…To exploit these properties of graphene in the miniaturized devices, controlled patterning of graphene films is essential as the performance of the devices highly depends on the quality of the produced patterns. Laser patterning is an attractive technique to do so and the laser parameters can be easily adjusted to obtain high quality patterns …”
Section: Introductionmentioning
confidence: 99%